On Optimal Production and the Market to Book Ratio Given Limited Shareholder Diversification - Conine, Thomas E.; Jensen, Oscar W.; Tamarkin, Maurry (Management Science, 1989)
Our purpose is to examine a firm's optimal output decision and valuation when its shareholders hold a limited number of risky assets. The primary theoretical result indicates that the market-to-book ratio is a function of the degree of shareholder diversification. Our theory suggests a negative relationship between a firm's market-to-book ratio and shareholder diversification.